Social presence as a training resource: comparing VR and traditional training simulations - Jakob Carl Uhl; Klaus Neundlinger; Georg Regal (Association for Learning Technology, 2023)
From immersive simulations to interactive tutorials, Virtual Reality (VR) is transforming the way we learn and practise new skills. Especially for social skills training, a growing number of simulations have been designed in which trainees learn to master difficult communicative situations. One of the factors to which the effectiveness of VR as a learning technology is attributed to is the users' feeling of social presence during the simulated interaction. This paper presents the evaluation of (1) a role play training, (2) a learning app and (3) a VR training application in a workshop series. Social presence was perceived as equally convincing and engaging for the prototypical VR scene as for the traditional form of role play, although the course of the interaction in VR was highly determined compared to the interaction dynamics of a human role play. In our interpretation, this confirms social presence as a valuable resource for training social interaction, which spans across various learning settings and methods in increasingly blended or hybrid learning and working contexts.